Ultrasound Changes of Postoperative Adhesion Types Over Time in Children - Alamdaran, Seyed Ali; Vahed, Seyed Hamidreza; Seyedin, Golnaz (Journal of Child Science, 2022)
Postoperative fibrotic band formation is a common complication that causes bowel obstruction, chronic pain, and especially reoperation problems. We tried to evaluate the ultrasound signs of different adhesions over time in children. This descriptive study was performed in children hospital of Mashhad University of Medical Sciences. Sixty-five children aged 4 months to 15 years (mean age of 7.2 ± 6.5 years) were enrolled in the study. Complete abdominal sonography using 5 to 12 MHz multifrequency probes was performed by a pediatric radiologist. The sonographic findings and data analysis were performed. In first week after surgery, the fibrinous exudates are seen as hypoechoic shadows. It has uneven thickness and usually encases the bowel loops in a circular shape. In second week, they gradually become straighter with uniform thickness. In this period, in 68% of cases, a hyperechoic line is formed in the center of hypoechoic fibrinous exudates, which is usually placed between the bowel loops (interloop fibrosis). The omentum or mesentery entrapment in the fibrinous exudates was occurred in ∼50% and 25% of these cases, respectively. In this state, echogenic omentum or mesentery was seen simultaneously with the hypoechoic fibrinous exudates. After 1 month from surgical procedure, One of the following four sonographic patterns are seen: attachment hyperechoic omentum to retroperitoneum (50%), attachment hyperechoic mesentery to anterior abdominal wall (26%), interloop fibrosis (39%), and severe hypoechoic fibrotic band (30%). Absence of visceral sliding was seen in 65 to 80% of patients. Overall, there are five morphologic patterns of adhesion on ultrasound: fibrinous exudates, interloop fibrosis, fibrotic band, fixed omentum to retroperitoneum, and fixed mesentery to abdominal wall.
Keywords: adhesion band; sonography; children